Associations between CYP2C8 rs10509681 and rs11572080 gene polymorphisms and age-related macular degeneration - Liutkevičienė, Rasa; Sungailienė, Ramunė; Vilkevičiūtė, Alvita; Kriaučiūnienė, Loresa; Vaitkienė, Paulina; Chaleckis, Romanas; Deltuva, Vytenis Pranas (Acta medica Lituanica, 2017)
Background. Age-related macular degeneration (AMD) is the most common cause of irreversible visual loss in industrialized countries. Early symptoms of AMD include drusen and changes in retinal pigment epithelium. However, the etiology of AMD and drusen formation is not fully understood. Recent studies suggest that CYP2C8-related metabolic processes might play an important role in the development of AMD. The aim of our study is to investigate CYP2C8 rs10509681 and CYP2C8 rs11572080 genotype frequencies in patients with early AMD and to compare them with healthy controls. Materials and Methods. The study enrolled 305 patients with early AMD and 300 healthy controls. The genotyping of CYP2C8 rs10509681 and CYP2C8 rs11572080 was carried out using the real-time PCR method. Results. The analysis of studied CYP2C8 polymorphisms did not reveal any statistically significant differences between the AMD and the control groups. For the CYP2C8 rs10509681 gene polymorphism the distribution of T/T, T/C, and C/C genotypes was 83.3%, 16.7%, and 0% vs. 83.7%, 15.7%, and 0.7%, p = 0.343. For the CYP2C8 rs11572080 gene polymorphism the distribution of C/C, T/C and T/T and genotypes was 84.9%, 15.1%, and 0% vs. 82.3%, 17.3%, and 0.3%, p = 0.447. Conclusion. The study revealed that there were no statistically significant differences in the distribution of CYP2C8 rs10509681 and CYP2C8 rs11572080 genotypes in patients with early AMD and in healthy controls.